1999
DOI: 10.1053/eupc.1998.0010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of accessory pathway and atrial refractoriness by transoesophageal and intracardiac atrial stimulation

Abstract: Asymptomatic dysfunction of cardiac pacing systems is not uncommonly detected using long-term ambulatory monitoring techniques. We report two patients with atrial and ventricular sensing abnormalities noted only on Holter monitoring. Multiple empirical attempts at pacemaker reprogramming based on deductive analysis of the pacing anomaly were unsuccessful. Through the use of a new digital recording system that allowed collection of surface electrocardiographic data, intracardiac electrograms, and Marker Channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It can also be used for risk evaluation in patients with pre-excitation, although a normal refractory period of the accessory pathway cannot rule out a risk of atrial fibrillation with a fast ventricular response [149,150] .…”
Section: Electrophysiological Testingmentioning
confidence: 99%
“…It can also be used for risk evaluation in patients with pre-excitation, although a normal refractory period of the accessory pathway cannot rule out a risk of atrial fibrillation with a fast ventricular response [149,150] .…”
Section: Electrophysiological Testingmentioning
confidence: 99%
“…Male gender, young age, sport, septal accessory pathway (AP), multiple accessory pathways, short AP refractory period, atrial fibrillation (AF) were reported as risk factors of sudden death in WPW syndrome [6,18,19]. Pappone and al considered only the induction of a re-entrant tachycardia or atrial fibrillation as a risk factor of arrhythmic events in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However 14 of these patients had later an intracardiac study and the variations of APERPs were similar. Nanthakumar et al [20] have compared transesophageal route and intracardiac rout at 24 hour interval. Despite adequate reproducibility, transesophageal atrial stimulation was shown to fail to predict the AP-ERP by intracrdiac stimulation.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This calculation has the advantage of providing the relationship between the variation of the observations and their magnitude expressed as a percentage. This variable has also been used in other studies evaluating the time‐dependent variation of electrophysiological variables in humans 11 . From a clinical standpoint, a reduction in the threshold of a magnitude sufficient to facilitate cardioversion and at the same time, cause the patient less discomfort, should probably be in the range of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies 7–10 have shown that rapid atrial pacing from a single site at a cycle length slightly shorter than that of the median fibrillation cycle length can achieve capture within 4–6 cm from the catheter tip and also affect left atrial activity recorded in the coronary sinus. Pacing through the coronary sinus electrode provides for epicardial pacing with a higher threshold and as a result endocardial pacing is preferred 11 …”
Section: Introductionmentioning
confidence: 99%